2017
DOI: 10.1039/c7ra10260g
|View full text |Cite
|
Sign up to set email alerts
|

Direct growth of a graphitic nano-layer on optical fibers for ultra-fast laser application

Abstract: A clean and uniform graphitic nano-layer (GNL) is grown in a controllable manner on the fiber-end by plasma-enhanced chemical vapor deposition. Using the GNL coated fiber, 991 fs soliton pulse generation at 1559 nm is achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Compared with the Fabry-Perot resonator without graphene, the graphene coating allows more light confined by the cladding leaking into the surrounding medium, and then the distribution of the evanescent field and spectral properties can be obviously modulated [25]. The graphene was grown on fibers by using radio-frequency plasma enhanced chemical vapor deposition technique (RF-PECVD) [31][32]. As shown in Fig.…”
Section: Device Design and Preparationmentioning
confidence: 99%
“…Compared with the Fabry-Perot resonator without graphene, the graphene coating allows more light confined by the cladding leaking into the surrounding medium, and then the distribution of the evanescent field and spectral properties can be obviously modulated [25]. The graphene was grown on fibers by using radio-frequency plasma enhanced chemical vapor deposition technique (RF-PECVD) [31][32]. As shown in Fig.…”
Section: Device Design and Preparationmentioning
confidence: 99%
“…Graphene, the most representative two-dimensional (2D) nanomaterial, has been extensively investigated as a SA in ultrafast photonics [15][16][17][18]. The unique properties of graphene, including massless Dirac fermions, low saturation intensity, broadband optical absorption, and fast relaxation mechanism make it an excellent material for mode-locked lasers [19][20][21][22]. Zhang et al reported on chemical vapor deposition (CVD) deposited graphene as the mode locker for the first time, which opened the door for using 2D materials as SAs in ultrafast photonics [23].…”
Section: Introductionmentioning
confidence: 99%